Impact of agriculture on water quality: a brief review - Santos, Marcela Granato Barbosa dos; Rocha, Guilherme Araujo; Portella, Aline Ramos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
The rapid growth of Brazilian agricultural production is only possible through the use of agricultural inputs, both mechanical (agricultural machinery and tractors) and chemical (pesticides and fertilizers). Unfortunately, agricultural intensification is accompanied by several potential sources of degradation of aquatic ecosystems. Thus, this work aims to present, in the form of a bibliographic review, the impacts that Brazilian aquatic ecosystems have been suffering in recent years, being extremely important to assist river basin managers in decision-making processes, and producers in the best choice of management, thus preserving the quality of Brazilian waters.